An uncommon cause of myalgia: A case report on systemic lupus erythematous myopathy - Shahleni Paramasivam; Malehah Mohd Noh; Mya Sanda Khaing; Izdihar Marwani Dahlan; Alvin Oliver Payus (Elsevier Ltd, 2022)
Introduction: Myositis in systemic lupus erythematous may present in a wide range of clinical spectrum. It can be part of an overlap syndrome, or mixed connective tissue disease or a musculoskeletal manifestation of systemic lupus erythematous itself. Case presentation: Here, we present a young girl with an underlying systemic lupus erythematous presented with the typical manifestation of severe proximal myopathy in the background of normal creatine kinase values. The diagnosis of systemic lupus erythematous myopathy was made after excluding other more common causes of myopathies which in itself is a very rare occurrence. Discussions: A normal creatine kinase values does not exclude systemic lupus erythematous myositis but make the diagnosis more challenging. However, there are other parameters or diagnostic tools which can be used to exclude a myositis.